Sosialisasi Penerapan Sistem Informasi Pendidikan untuk Pengelolaan Data Guru dan Akademik Berbasis Web - Sayuti, Akhmad; Irwansyah; Abdul Harits M; Serry Davizan; Bella Paramita (Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2024)
This article aims to introduce and implement a Web-Based Information System at SMK Bina Sriwijaya, Palembang. Through socialization and training activities, participants from various backgrounds, including teachers, students, operators, administrators, school principals, and parents, were invited to understand and use this system. The implementation method of the activities includes preparation, execution, and evaluation stages. The results showed that participants demonstrated enthusiasm in understanding and using this system. With the presence of a web-based information system, it is expected that the effectiveness and efficiency of academic and administrative data management in schools can be improved, providing faster and more accurate information, and minimizing possible errors. In conclusion, this activity successfully introduced and implemented a Web-Based Information System at SMK Bina Sriwijaya, which is expected to make a positive contribution to the management of academic and administrative data in the school.